Health and Safety Risk Analysis of Iron Fabrication Work Using Job Safety On The Medan Merdeka Field Revitalization Project - Giranza, Virgian; Prasetyo, Angga Dwi; Zahara, Mila; Harahap, Reni Agustina; Faris, Tengku Muhammad; Araafi, Alif; Wahyudi, Saidana Putra (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Job Safety Analysis (JSA) aims to improve workplace safety by identifying potential hazards in a job or process. Through this analysis, each stage of the job can be evaluated for risk so that appropriate precautions can be taken to prevent accidents or incidents from occurring. The purpose of this study is to analyze a series of iron fabrication activities to find sources of danger and how to control these hazards. This research is qualitative research. The research data used are primary data and secondary data. The data collection methods are interviews, documents, and observations, direct observation of the iron fabrication work division of the Medan Merdeka Field Revitalization project. Data processing was conducted by this research using Job Safety Analysis (JSA). The results of the study found that the hazard that often arises in iron fabrication work is pinched. This is because the stages of work, starting from iron slicing, transporting iron to the machine, and operating the machine, have the potential for pinched hazards that can be experienced by workers, such as limbs that can be pinched by iron, limbs that can be pinched by bar cutting machines, and fingers that can be pinched by bar bending machines. There are hazards that iron fabrication workers must be aware of, namely physical, mechanical, electrical, and ergonomic hazards. Keywords: Iron Fabrication, JSA, Pinch, Work Accident